Analysis of determinants of firm value: a study of listed companies in the tobacco sub-sector on the Indonesia Stock Exchange (2012-2024) - Andre Atmaga Turnip; Sila Patrisia; Didik Gunawan; Willy Cahyadi (Institute of Computer Science (IOCS), 2026)
This study aims to analyze the effects of profitability (ROA), leverage (DER), and liquidity (CR) on firm value, as measured by Tobin's Q, among companies in the tobacco subsector listed on the Indonesia Stock Exchange during the period 2012-2024. A quantitative causality approach was employed using the Ordinary Least Squares (OLS) multiple linear regression method with Heteroscedasticity and Autocorrelation Consistent (HAC) standard errors using the Newey-West estimator (Bartlett kernel, fixed bandwidth = 4) on three sample companies: PT Gudang Garam Tbk (GGRM), PT Hanjaya Mandala Sampoerna Tbk (HMSP), and PT Wismilak Inti Makmur Tbk (WIIM), with a total of 39 observations. The results indicate that, both partially and simultaneously, profitability, leverage, and liquidity do not significantly affect firm value (p > 0.05; Wald F-statistic = 0.776; Prob. 0.515). An R-squared value of 10.96% indicates that most of the variation in firm value is explained by factors outside the model that influence market sentiment. This finding underscores the uniqueness of the tobacco industry as a sector facing multi-dimensional pressures that cannot be fully captured through conventional financial ratios